2009
DOI: 10.1590/s1806-37132009000700004
|View full text |Cite
|
Sign up to set email alerts
|

The study of severe asthma in Latin America and Spain (1994-2004): characteristics of patients hospitalized with acute severe asthma

Abstract: Objective: Studies assessing the characteristics and management of patients hospitalized with asthma have been limited to a small number of facilities and have evaluated short time periods. The present study evaluated long-term changes among hospitalized asthma patients at a large number of facilities. Methods: This was a retrospective, hospital-based observational case series, designated the Study of Severe Asthma in Latin America and Spain, which was conducted in Spain and in eight Latin-American countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
(25 reference statements)
0
10
1
Order By: Relevance
“…Although a definition of status asthmaticus is available,14 there are several different terms, including acute asthma, severe asthma, and hospital admission due to asthma 2,5,17,1922,24,25,38. Furthermore, status asthmaticus is the only sub-code among the asthma diagnoses in the ICD-10 that denotes an acute asthmatic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Although a definition of status asthmaticus is available,14 there are several different terms, including acute asthma, severe asthma, and hospital admission due to asthma 2,5,17,1922,24,25,38. Furthermore, status asthmaticus is the only sub-code among the asthma diagnoses in the ICD-10 that denotes an acute asthmatic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Rodrigo et al showed us that the mean hospital stay was one week, which, obviously, results in an equal duration of work absenteeism. (1) In terms of the hospitalization of patients with severe asthma, the popular adage "Time is money" has been confirmed in studies conducted in Brazil. One year after asthma had been included in a program of control, including pharmacological treatment at no charge to the patient, there was a reduction in the number of asthma-related hospitalizations and emergency room visits, as well as an improvement in asthma "Medicaments au Nord, malades au Sud..."…”
mentioning
confidence: 98%
“…That statement, which remains valid, can also be applied to asthma, for a variety of reasons, including the failure of many governments and government officials to recognize the extent and repercussions of this disease. This is illustrated in the study conducted by Rodrigo et al, published in this issue of the Brazilian Journal of Pulmonology, (1) in which the authors profiled patients with acute severe asthma, hospitalized in Spain or in one of a number of Latin-American countries. Mutatis mutandis, many of their findings reflect the fact that, south of the equator, budgets established for the health sector in general, as well as for increasing the availability of essential medications in particular, are insufficient.…”
mentioning
confidence: 99%
See 2 more Smart Citations